Assembleia de aves em dois fragmentos florestais no interior do estado de São Paulo - Paes de Barros, Marcelo [UNESP] (2015)
The aim of this study was to analyze and to compare birds' communities in two forest fragments in the state of São Paulo, from qualitative and quantitative surveys. And also compare the results of the parameters studied with other works of the same nature and sampling effort and analyze the use of the bird community as environmental quality bio-indicators and state of conservation of forest fragments studied. Forest fragments were studied in the west of the state, with approximately 300 hectares, varying in shape, distance and isolation of these other fragments. The qualitative survey consisted of extensive studies in the area itself and surrounding areas, where all species of birds seen and heard were recorded and information as wealth, frequency of occurrence and similarity were recorded. But the qualitative survey was based on the methodology of counting by listening posts, which analyzed parameters such as wealth, abundance, similarity, diversity and functional groups. The field work have been developed for 12 months in each area and compared to similar works by other researchers in order to better understand the observed data. The survey showed that the number of species recorded in the Mata do Peixe fragment was higher than the Cristal fragment, and also higher than in work on bird communities in secondary forests fragments made by other authors. This fragment had a lower number of unique species and mostly treated forest species habits outlined environmental requirements. Unlike Cristal fragment, where many species have few records and mostly species are open areas and low sensitivity to environmental disturbances. It was found that the two areas suffer from forest fragmentation when presenting many species of birds living in forest edges and population imbalances in your community of birds, as poor results of detritivores birds and nectarivores. Due to the characteristics of the fragments and the comparison with similar work, ...